PERANAN AUDITING DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE ( GCG ) DITINJAU DARI AUDIT INTERN DAN KOMITE AUDIT - MARYONO (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2020)
Good corporate governence is a form of good corporate governance. With good governance expected thecompany will increase. In achieving good corporate governence interanal audit and audit committeeplays an important role. Internal audit and the audit committee is an interface between the company,commissioners and shareholders, as well as controllers and evaluators running of the company. Inachieving good corporate go vernence there are several constraints, the presence of internal audit andaudit committees are expected to reduceall forms off raudand irregularities. However,internal audit andaudi tcommittee is not the only tool to reduce fraud and irregularities including good internal controlsystemal so plays a role.